Um tipo diferente de animal: como a cultura transformou nossa espécie - Tryjanowski, Piotr; Hromada, Martin; Angeoletto, Fabio (Terr@ Plural, 2019)
BOYD, Robert. A different kind of animal: how culture transformed our species. Princeton University Press, 2017. 248 p.